Effectiveness of Malaysian Property Maintenance and Management Outsourcing - Chin Sheng, Lee; Ahmad Baharum, Zarita (International Journal of Property Sciences (E-ISSN: 2229-8568), 2015)
The effectiveness of outsourcing implementations and practices in the property maintenance and management (PMM) sector in Malaysia needs to be investigated and service chasm to be ascertained for the improvement and development of the industry. A survey was conducted among outsourcing clients and outsourcing service providers to determine the effectiveness of current services provision. A quantitative method by means of survey questionnaire is used in investigating the PMM outsourcing effectiveness and implementations in practice. Chasm analysis which stemmed from the mean result derived from the study depicts the ineffectiveness of the current PMM services outsourcing implementations and practices. Outsourcing effectiveness criteria of quality and risk and liabilities appeared to be at the top of the list on mean difference analysis between outsourcing clients and outsourcing service providers. Outsourcing service provider should be aware of this perception gap for their subsequent mitigation and improvement planning. Priority should be given to those effectiveness criteria with the largest mean difference gap from the analysis. The paper provides empirical data for PMM services outsourcing practitioner in Malaysia for their insight on the current services performance and effectiveness level. The result will aid service providers in strategizing future direction and improvement planning of respective firm and enhance the services delivery to outsourcing client.